REPRODUCTIVE CHRONOLOGY, SPRING HUNTING, AND ILLEGAL KILL OF FEMALE WILD TURKEYS - Gary W. Norman; David E. Steffen; Curtis I. Taylor; James C. Pack; Kenneth H. Pollock; Kuenhi Tsai (Wildlife Society Bulletin)
Abstract: We investigated aspects of gobbling chronology, nesting chronology, illegal kill of females, and overall survival of female eastern wild turkeys (Meleagris gallopavo silvestris) under different spring season formats in Virginia and West Virginia. Gobbling rates were determined from survey routes in Virginia prior to spring hunting during 1958–60 and from surveys of spring hunters in Virginia and West Virginia during 1990–98. Patterns of gobbling activity observed on routes during 1958–60 differed from those reported by hunters during 1990–98. The number of gobbling males heard/route in years prior to spring hunting was greatest from mid‐April to early May while gobbling males heard/100 hr by hunters declined from opening date of the spring season in mid‐April through May. Mean gobbling and nesting dates were related over 5 years in Virginia and West Virginia (P = 0.08). Known illegal kill of females averaged 2.5 ± 0.8% in West Virginia and 6.0 ± 1.3% in Virginia. Differences in survival distributions due to illegal mortality between states over the 5‐year study (P = 0.011) and a negative relationship between illegal mortality rates and opening date of spring seasons (P = 0.005) suggest that timing of the spring season contributed to the difference in illegal mortality rates between states. Overall spring survival rates of females in Virginia (Ŝ = 0.832 ± 0.019) were not different from West Virginia (Ŝ = 0.794 ± 0.016). Survival rates of nesting (Ŝ = 0.904 ± 0.017) and nonnesting birds (Ŝ = 0.874 ± 0.020) were similar. Spring seasons that begin during or after egg laying may coincide with gobbling chronology and reduce the potential for illegal kill of females.